The Impact of Applying Governance on Improving the Performance of Employees in Palestinian Ministries - Karajah, Lorees Mofid; Iriqat, Ismail (The Arab Journal of Administration, 2025)
This study aims to define the governance of ministries, its principles, importance and objectives, and to know its role in raising the performance of workers in Palestinian ministries, and since there is no agreement on the concept of governance, but there is agreement that its application enhances the efficiency of performance, so any ministry that implements it supports its ability to face any crisis It confronted and objected to it, and worked to highlight the role of the independent variable “governance principles on the dependent variable “employee performance”, and this was evident in this research through the application of the six principles of governance, where the researcher assumed that the application of governance principles contributes significantly to improving the performance of employees and the results of the questionnaire analysis came Investigator of the study hypotheses. The researcher relied on the descriptive analytical approach (quantitative), the study relied on data collection and analysis in its primary sources, and the questionnaire of the specialists as a tool for the study, and the questionnaire was applied to the study sample, where five ministries were relied on using the soft sample, and 25 employees were selected from Each ministry, and reviewing Arab and foreign theoretical and field studies related to the subject, with an extrapolation of its most important results. The results of the questionnaire analysis showed that the application of the principle of (accountability, justice, transparency, integrity, rule of law and participation) contributes significantly to improving the performance of workers in Palestinian ministries. By holding training workshops to educate employees, as well as enacting the necessary laws that ensure the application of all employees to these principles, punishing violators and applying the law to everyone without discrimination.